The prevalence and patterns of rationing of nursing care in acute care settings - Dimitriadou, Maria; Vryonides, Stavros; Papastavrou, Evridiki (My University, 2018)
When resources are insufficient, nurses are forced to ration their attention between care activities with the potential consequence of withholding or failing to carry out certain nursing activities. As a result fundamental patient needs may not be fulfilled leading to adverse patient outcomes (ie: falls, and nosocomial infections). Evidence suggests that individual nurse and patient related characteristics as well as environmental factors can initiate rationing. The aim of the study was to describe and compare the frequency of implicit rationing of nursing care in different clinical settings in Cyprus and identify any relevant environmental factors. Three descriptive, correlational cross-sectional studies were involved. Data were collected using the BERCNA questionnaire from 393 nurses working in medical and surgical units. One hundred and fifty seven nurses working in oncology units responded to a ‘Missed Care’ questionnaire, and data were also data collected from 540 nurses in 14 general medical and surgical wards across five public hospitals, who responded to the question task undone (TU-13) as part of the RN4CAST-cy project. The response rate of all the studies was >60% of the samples. Despite the the use of three different instrumentations, there were similar patterns of implicit rationing. Findings reveal that activities described as frequently or always left undone were: mouth care (61.1%); Comfort/talk with patients (58.3%), educating patient or families (54.0 %); emotional and psychological support (32.5%); and reviewing patient documentation (31%). Environmental dimensions, such as ‘teamwork communication about patients’ were associated with a decreased level of rationing. Nursing care left is a significant problem in acute care hospitals. Rationing of care creates two problems. Firstly it leaves patients vulnerable to unmet educational, emotional, and psychological needs. Secondly, it leaves nurses vulnerable to unmet received knowledge as they lack sufficient information about the patient situation and this may lead to false decisions in prioritising care.
Keywords: Implicit rationing; Nursing care